GeoCongress 2012 2012
DOI: 10.1061/9780784412121.083
|View full text |Cite
|
Sign up to set email alerts
|

On Some of the Factors Influencing the Fines' Role on Liquefaction of Silty Sands

Abstract: Silty sands are among the soil types that are prone to liquefaction when subjected to static or dynamic undrained loading. Today, it is widely accepted that clean sands and silty sands react differently in terms of liquefaction behavior. With this observation, factors influencing fines' role on such a difference have been investigated by various researchers. Some of those factors such as laboratory specimen preparation method and confining stress are relatively well understood. However, some others such as fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another explanatory approach is the PDI (see Table 1 ): the higher the PDI , i.e., the more polydisperse and inhomogeneous the system, the denser the packing can become. All these observations show that small particles are most influential on the engineering response of the terrestrial and therefore lunar soils [ 101 ].…”
Section: Properties Of Lunar Regolith Simulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanatory approach is the PDI (see Table 1 ): the higher the PDI , i.e., the more polydisperse and inhomogeneous the system, the denser the packing can become. All these observations show that small particles are most influential on the engineering response of the terrestrial and therefore lunar soils [ 101 ].…”
Section: Properties Of Lunar Regolith Simulantsmentioning
confidence: 99%
“…The x 50 of the three simulants ranges from 76.7 to 96.0 µm (see Table 2 ), and thus, in terms of particle count, there are relatively few coarse grains (though high masses) in the mixture. Moreover, the high proportion of small grains (within the mixture) indicates that the finer fractions significantly influence the overall behavior of the regolith simulants [ 101 ].…”
Section: Properties Of Lunar Regolith Simulantsmentioning
confidence: 99%
“…The soil liquefaction strength may also vary with the fines content. Numerous studies concluded that anti-liquefaction of soil susceptibility is greatly affected by fines content [33][34][35]. As fines content exceeds 30%, soil liquefaction potential increases.…”
Section: Fines Contentmentioning
confidence: 99%